A Bibliometric Analysis of Current Trend on Research for Design and Furniture Indusry in The Perspective of Business Strategy - Alidha Nurhalima; Mahendra Wardhana; Berto Mulia Wibawa (Green Publisher Indonesia, 2025)
This study aims to explore current trends and emerging patterns in the design and furniture industry, focusing on business strategy. Specifically, it seeks to analyze aspects such as sustainability, innovation, and consumer-centric strategies, highlighting how these factors influence industry resilience and adaptability. A comprehensive bibliometric analysis is conducted using the Biblioshiny program on Rstudio. This method provides insights into the evolving landscape of the design and furniture industry through an examination of relevant literature and research patterns. The analysis reveals a strong emphasis on sustainability, innovation, and consumer-oriented strategies within the design and furniture industry. Key strategies include adapting interior designs, implementing green marketing practices, and utilizing digital technologies. These approaches enable the industry to address changing market demands. However, integrating business strategies also poses challenges such as resource limitations and sustainability issues. This study contributes to the theoretical understanding of business strategy in the design and furniture industry by identifying critical research trends and gaps. It highlights the importance of sustainability and consumer-centered approaches, providing a foundation for future research on the impact of these strategies on industry practices. Findings suggest practical implications for industry stakeholders, including the need for sustainable practices, consumer-centric strategies, and technological adoption. Policymakers and practitioners can use this knowledge to foster industry resilience and support sustainable growth in the design and furniture sector. The study is limited to a bibliometric analysis, which provides an overview of existing literature without empirical validation.